2005
DOI: 10.1002/ps.1034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grain type on the insecticidal efficacy of two diatomaceous earth formulations against Rhyzopertha dominica (F) (Coleoptera: Bostrychidae)

Abstract: Laboratory bioassays were carried out in order to evaluate the effectiveness of two diatomaceous earth (DE) formulations, Insecto and SilicoSec, against adults of Rhyzopertha dominica (F) in eight different grain commodities. The adherence of the two DEs to each grain was also measured. The eight grains tested were wheat, whole barley, peeled barley, oats, rye, triticale, rice and maize. These commodities were treated with the DEs at three rates, 0.75, 1.0 and 1.5 g DE kg(-1) grain. The mortality of R dominica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 128 publications
(66 citation statements)
references
References 23 publications
(34 reference statements)
3
59
0
4
Order By: Relevance
“…Our results are in agreement with the findings of La Hue [24], Wakil et al [25 ] and Athanassiou et al [26] who also reported that adult mortality increased with increase in dose rate and exposure period, and efficacy varied between grain types. Variations in efficacy of DEs among different grain types has been noted in a series of recent studies, involving tests with different DE products on different grain types [14,15,27,28]. The significant interaction effect (P<0.001) between dose rate and grain type on mortality of R. dominica noted in this study, confirms the aforementioned statements that DE efficacy is influenced by grain type.…”
Section: Resultssupporting
confidence: 87%
“…Our results are in agreement with the findings of La Hue [24], Wakil et al [25 ] and Athanassiou et al [26] who also reported that adult mortality increased with increase in dose rate and exposure period, and efficacy varied between grain types. Variations in efficacy of DEs among different grain types has been noted in a series of recent studies, involving tests with different DE products on different grain types [14,15,27,28]. The significant interaction effect (P<0.001) between dose rate and grain type on mortality of R. dominica noted in this study, confirms the aforementioned statements that DE efficacy is influenced by grain type.…”
Section: Resultssupporting
confidence: 87%
“…One of the most promising alternatives to synthetic contact insecticides in stored product protection is the application of diatomaceous earth (DE) (Fields and Korunic 2000;Vayias and Athanassiou 2004;Athanassiou et al 2005;Kavallieratos et al 2005). Although several modes of action have been proposed (Subramanyam and Roesli 2000), it is today generally accepted that damage occurs to the protective wax layer in the insect's cuticle, resulting in water loss and desiccation (Mewis and Ulrichs 1999;Subramanyam and Roesli 2000).…”
Section: Introductionmentioning
confidence: 98%
“…It is not known whether the results obtained in this study would hold true under different conditions. Perhaps different results may be obtained if the DE were to be tested on grains other than wheat or maize because DE efficacy is known to vary among grain types [4,5,16,32]. The susceptibility of a given species to DE might be influenced by the insect strain [33].…”
Section: Discussionmentioning
confidence: 99%
“…temperature [2,[14][15][16], moisture content or relative humidity [15,[17][18][19], and type of grain commodity [4,20,21]. Laboratory experiments have also revealed significant effect of insect species [15], insect strain [22,23], stage [19,24].…”
mentioning
confidence: 99%